2018
DOI: 10.1186/s40594-018-0126-3
|View full text |Cite
|
Sign up to set email alerts
|

Connection between academic emotions in situ and retention in the physics track: applying experience sampling method

Abstract: BackgroundThere is a lack of students enrolling in upper secondary school physics courses. In addition, many students discontinue the physics track, causing a lack of applicants for university-level science, technology, engineering and mathematics (STEM) programmes. The aim of this research was to determine if it is possible to find a connection between academic emotions in situ and physics track retention at the end of the first year of upper secondary school using phone-delivered experience sampling method. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…As a concrete example, building conceptual links between history and physics and presenting students with reconstructions about the historical role of physics experiments of the 19th century has been indicated as a rather powerful way of favoring physics teaching [35]. Although resistance-to-change [48] poses a challenge for innovating teaching styles and curricula, the advent of tools reducing anxiety and favoring concentration in students is important not only for its self-evident psychological benefits but also in terms of facilitating and enhancing students' performance in STEM [6,4] and students' appreciation of STEM careers [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a concrete example, building conceptual links between history and physics and presenting students with reconstructions about the historical role of physics experiments of the 19th century has been indicated as a rather powerful way of favoring physics teaching [35]. Although resistance-to-change [48] poses a challenge for innovating teaching styles and curricula, the advent of tools reducing anxiety and favoring concentration in students is important not only for its self-evident psychological benefits but also in terms of facilitating and enhancing students' performance in STEM [6,4] and students' appreciation of STEM careers [15].…”
Section: Discussionmentioning
confidence: 99%
“…Increasingly more studies in Education Science suggest that a large number of students experience anxiety while in educational settings [1,2,3,4,5]. Stress can arise from multiple sources.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Values of the odds ratio greater than 1 mean that as the predictor variable increases, so do the odds of having academic achievement (e.g. Alzen et al, 2018;Lehtamo, Juuti, Inkinen & Lavonen, 2018).…”
Section: Analysesmentioning
confidence: 99%
“…Biology education researchers have also noted that women in introductory biology were more affected by negative academic emotions that could lead them to self-deprecating cycles [30]. Studies in PER have revealed links between emotions of control (e.g., frustration, calmness) to performance [31]; emotions towards physics topics to engagement [32]; stress to retention [33]; and emotions to shifts in reasoning [34,35]. These correlations between emotions and learning highlight the value of considering emotions in PER to better understand their effect on learning.…”
Section: A Guiding Frameworkmentioning
confidence: 99%